Educational and training interventions aimed at healthcare workers in the detection and management of people with mental health conditions in South and Southeast Asia: systematic review protocol. Issue 7 (2nd July 2021) - Koly, Kamrun Nahar; Baskin, Cleo; Lata, Ivy; Rao, Mala; Rasheed, Sabrina; Law, Graham; Gnani, Shamini
Abstract : Introduction: The mental health burden and treatment gap in South and Southeast Asia is high and significant. Capacity building of healthcare workers is essential to support programmes related to the detection and management of patients with mental health conditions. We aim to conduct a systematic review to summarise the research on educational, training and capacity-building interventions aimed at the healthcare workforce in detection and management of mental health conditions in South and Southeast Asia. Objective: To synthesise evidence on (1) the types of educational and training interventions that have been used to improve the knowledge, skills and attitudes of healthcare workers in South and Southeast Asian countries in the detection and management of mental health conditions; (2) the effectiveness, including cost-effectiveness of the interventions; and (3) the enabling factors and barriers that influence the effectiveness of these interventions. Methods and analysis: This review will be conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews guidelines. We will search six electronic databases: MEDLINE, EMBASE, PsycINFO, Cochrane Library, Cumulative Index to Nursing and Allied Health Literature, and Global Health for empirical studies published from 1 January 2000 to 31 August 2020. Search results from each database will be combined and uploaded in Covidence library. Title, abstract and full-text screening, and data extraction of each included study will be performed by two independent reviewers. Disagreements between reviewers will be resolved by a third reviewer and study team. Quality of included studies will be assessed by the modified Cochrane Collaboration tool and ROBINS-I tool. Data will be synthesised and if a meta-analysis is not appropriate, a stepwise thematic analysis will be performed. Ethics and dissemination: Ethics approval is not required for this study. Findings will be disseminated through peer-reviewed publications, fact sheets, multimedia press briefings, conferences, seminars and symposia. PROSPERO registration number: CRD42020203955.